Terminology (and) Translation:: the transdisciplinary dialogue in Intermediality (Intercom - Brazilian Journal of Communication Sciences, 2024)
The task of translation, although enriched by different experiences, can often lead to conflicting choices, which hinder dialogue between academics who come from different fields of research, giving rise to reasons for divergences. In this work, we will present some elements from the experience of translating the terminology proposed by Lars Elleström, for example, of concepts related to the transfer of media characteristics between different media, comparing and contrasting them with other familiar terminologies, such as the notions of “transmediality”, by Irina Rajewsky, “transmedia storytelling”, by Henry Jenkins, and “remediation”, by Jay David Bolter and Richard Grusin. Our objective is to present some of the possibilities of finding common ground for the terminology on Intermediality in Portuguese, enabling a more productive interdisciplinarity.
Keywords: Terminology; Intermediality; Transmediality; Translation; Lars Elleström